Motor fiber function in spinal muscular atrophy—analysis of conduction velocity distribution - Koszewicz, Magdalena; Ubysz, Jakub; Dziadkowiak, Edyta; Wieczorek, Malgorzata; Budrewicz, Slawomir (Frontiers in Neurology, 2023)
Objectives: The motor neuron survival protein, which is deficient in spinal muscular atrophy (SMA), performs numerous cellular functions. Currently, SMA is believed to be a multi-organ disease, including lesion of various structures of the central and peripheral nervous systems. Motor nerve damage, especially in milder SMA types, is controversial. This prompted the conduct of the electrophysiological studies in adults with SMA types 2 and 3 presented in this paper. Methods: The study group consisted of 44 adult patients with SMA types 2 and 3. All patients underwent neurological examination with Hammersmith Functional Motor Scale – Expanded (HFMSE) assessment. Standard electrophysiological studies in the ulnar nerve and conduction velocity distribution (CVD) tests were performed in all patients and controls. Results: A prolongation of the distal latency and lowering of the motor potential amplitude with no changes in CVD were found in the whole patient group. There were no dependencies on the number of gene copies. Patients with low HFSME value had slower standard conduction velocity, CVD in upper and median quartiles, and narrower CVD spread; in milder SMA, CVD spread was greater than in controls. Interpretation: The significant reduction in motor response amplitude in SMA seems to be primarily related to motor neuron loss and directly proportional to its severity. The coexisting rearrangement in the peripheral nerve structure is present in SMA, and this could be partially caused by a coexisting demyelinating process. Nerve remodeling mainly affects large fibers and occurs in more severe SMA types with significant disability.